(untitled) (SCIENCE TIME JOURNAL, 2026)
In modern linguistics, paremiological units, that is, proverbs and sayings, are studied not only as examples of folklore, but also as linguistic units that carry profound cultural, cognitive, and semantic information. Paremiological units reflect not only spiritual values and traditions, but also the structure of national consciousness. Through them, the historical memory of a people, their observations of social life, ethical norms, and emotional experiences are expressed. This article analyzes the key components in English and Karakalpak proverbs from the perspective of semantic shift, metaphorical features, and cultural connotations.